Work-Life Balance in Female Health Professionals: A Phenomenological Study on Challenges, Strategies and Experiences of Making Time for Oneself - Bilengül Şiğra Elmas; Nurten Gülsüm Bayrak (Middle Black Sea Journal of Health Science, 2026)
Objective: The aim of this study is to deeply examine the work-life balance experiences of female healthcare professionals, the challenges they face in this process, the coping strategies they develop, and their time management practices.Methods: The research was conducted using a phenomenological design, one of the qualitative research methods, with 18 female healthcare professionals working in different healthcare fields in Türkiye. Participants were recruited using a snowball sampling method, and data were collected through semi-structured, in-depth individual interviews. The data were analyzed using Colaizzi's seven-stage phenomenological method, with two researchers independently coding the data and reaching consensus on themes and sub-themes.Results: Content analysis revealed three main themes: responsibilities and work-life balance, work-related challenges, and coping strategies, comprising eight sub-themes: burden of responsibility, work system and order, psychological, physical, and social challenges, individual coping methods, support factors, and time management. Female healthcare professionals struggle to balance professional and family responsibilities, leading to guilt, burnout, and delayed self-care. Institutional support and individual coping strategies partially buffered this burden, although postponement of self-care and weak social support limited their protective effect.Conclusion: These findings support strengthening work-life balance policies in healthcare institutions and increasing psychosocial support for female healthcare workers.